Modulation of Ion Transport Across Plant Membranes by Polyamines: Understanding Specific Modes of Action Under Stress - Pottosin, Igor; Olivas-Aguirre, Miguel; Dobrovinskaya, Oxana; Zepeda-Jazo, Isaac; Shabala, Sergey (Frontiers in Plant Science, 2021)
This work critically discusses direct and indirect effects of natural polyamines and their catabolites such as reactive oxygen species and - aminobutyric acid, on the activity of key plant ion-transporting proteins such as plasma membrane H+ and Ca2+ ATPases and K+-selective and cation channels in plasma membrane and tonoplast, in the context of their involvement in stress responses. Docking analysis predicts a distinct binding for putrescine and longer polyamines within the pore of vacuolar TPC1/SV channel, one of the key determinants of the cell ionic homeostasis and signaling under stress conditions, and an additional site for spermine, which overlaps with the cytosolic regulatory Ca2+-binding site. Several unresolved problems are summarized, including the correct estimates of the subcellular levels of polyamines and their catabolites, their unexplored effects on nucleotide-gated and glutamate receptor channels of cell membranes and Ca2+-permeable and K+ -selective channels in membranes of plant mitochondria and chloroplasts, and pleiotropic mechanisms of polyamines´ action on H+ and Ca2+ pumps.